O5-S4.04 Targeted STD screening among high-risk men who have sex with men. (10th July 2011) - Perkins, R; Furness, B; Hager, M; McLaughlin, R; Goforth, J; Davies, M
Abstract : Background: Subgroups of men who have sex with men (MSM) are at high risk for HIV infection and other viral and bacterial STDs. Since the mid-1990s, increased rates of early syphilis, gonorrhoea, and chlamydial infection and higher rates of unsafe sexual behaviours have been documented among MSM in the USA and virtually all industrialised countries. Methods: The Gay Men's Health & Wellness (GMH&W) Clinic is a Tuesday and Thursday evening STD clinic for men at Whitman-Walker Clinic (WWC), a Washington, DC community health center specialising in HIV/AIDS care and lesbian, gay, bisexual, and transgender care. As an outreach of this bi-weekly clinic, WWC, Gilead Foundation, and the local HIV/AIDS, Hepatitis, STD, and TB Administration collaborated to provide STD screening in the Crew Club, the District's only bathhouse serving MSM, for ∼4 h each Tuesday night beginning July 2010. All participating men were offered HIV screening, syphilis screening, and nucleic acid amplification testing NAAT) for gonorrhoea and chlamydia of urine, pharyngeal, and rectal specimens. Results: During the first 6 months of testing at the Crew Club, 173 unique clients were screened. Of those, five new HIV and 18 new syphilis cases were identified (Abstract O5-S4.04 table 1 ). In addition, two urethral, six pharyngeal, and two rectal gonorrhoeal infections were identified and five urethral, two pharyngeal, and 14 rectal chlamydial infections were identified. In comparison, during 2010, 2487 unique clients were tested at the GMH&W Clinic. Of those, 37 HIV and 189 syphilis cases were identified. In addition, 115 urethral and 89 rectal gonorrhoeal infections were identified and 139 urethral and 124 rectal chlamydial infections were identified. Pharyngeal results from the GMH&W Clinic were not yet available. Conclusions: A higher percentage of presumably asymptomatic clients tested positive for HIV and syphilis infections during STD screening in this non-traditional venue than during the diagnosis and routine screening that occurred at the clinic. Conversely, a higher percentage of clients, many of whom were symptomatic, tested positive for gonorrhoea and chlamydia during the GMH&W Clinic than during the Tuesday night outreach. This effort allows us to engage hard-to-reach men who may be among the core transmitters driving the HIV and syphilis epidemics in the DC area. Costs per HIV and syphilis cases detected need to be calculated /estimated for this fruitful outreach endeavour.